The development of a double wind turbine with sail wind wheels placed at right angle to one another - Kussaiynov, K.K.; Sakipova, S.E.; Kambarova, Zh.T.; Turgunov, M.M. (Publishing House of the KarSU named after E.A.Buketov, 2015)
To address the problem of increasing the operation efficiency of the wind turbine with dynamically changeable shape of blades when there is no constant wind direction, in work double wind turbines placed perpendicular to each other was studied. In this case, the entire working "circle" of wind directions is completely covered by two wind turbines. The total contribution of each wind turbine at all directions of the wind gives a permanent result of generated power. The results of the test model of the double wind turbine to determine the aerodynamic characteristics.
Keywords: double wind turbine; sail wind wheel; renewable energy sources; aerodynamic characteristics; thrust force